INTEGRASI SISTEM INFORMASI KESEHATAN DI DINAS KESEHATAN KABUPATEN BATANGHARI PROVINSI JAMBI TAHUN 2025 - Marlindawati, Marlindawati; Pramudho, P.A. Kodrat; Andarini, Sari Yuli (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
The utilization of electronic-based technology (e-government) is a key strategy for promoting effective, transparent, and accountable governance, including in the health sector. The implementation of the Electronic-Based Government System (SPBE) and health information systems plays a crucial role in producing accurate and timely data to support decision-making. This study aims to analyze challenges in the collection and management of the Integrated Recording and Reporting System of Primary Health Centers (SP2TP) at the Batanghari District Health Office, which is still conducted manually, and to formulate a more effective reporting model. A qualitative approach was employed through in-depth interviews, observations, and document reviews involving 14 informants. The findings identified five main themes: health information systems, SP2TP utilization, data integration, challenges, and solutions. Key problems included the absence of a centralized database, limited infrastructure, and insufficient human resources with information technology competencies. SWOT analysis revealed strengths in the utilization of the E-Puskesmas application and national policy support, while major constraints involved fragmented applications and budget limitations. Improvement strategies include short-term solutions using basic cloud platforms and long-term development of an integrated web- and cloud-based reporting system to enhance data integration and governance performance. ABSTRAKPemanfaatan teknologi berbasis elektronik (e-government) menjadi strategi penting dalam mewujudkan tata kelola pemerintahan yang efektif, transparan, dan akuntabel, termasuk di sektor kesehatan. Penerapan Sistem Pemerintahan Berbasis Elektronik (SPBE) dan sistem informasi kesehatan berperan krusial dalam menyediakan data yang akurat dan tepat waktu sebagai dasar pengambilan keputusan. Penelitian ini bertujuan menganalisis permasalahan pengumpulan dan pengelolaan data Sistem Pencatatan dan Pelaporan Terpadu Puskesmas (SP2TP) di Dinas Kesehatan Kabupaten Batanghari yang masih dilakukan secara manual, serta merumuskan model pelaporan yang lebih efektif. Penelitian menggunakan pendekatan kualitatif melalui wawancara mendalam, observasi, dan telaah dokumen terhadap 14 informan. Hasil penelitian mengidentifikasi lima tema utama, yaitu sistem informasi kesehatan, pemanfaatan SP2TP, integrasi data, tantangan, dan solusi. Permasalahan utama meliputi ketiadaan basis data terpusat, keterbatasan infrastruktur, dan minimnya sumber daya manusia berkompetensi teknologi informasi. Analisis SWOT menunjukkan adanya potensi dari pemanfaatan E-Puskesmas dan dukungan kebijakan nasional, namun masih terkendala fragmentasi aplikasi dan keterbatasan anggaran. Strategi perbaikan mencakup solusi jangka pendek berbasis cloud sederhana serta pengembangan sistem pelaporan terintegrasi berbasis web dan cloud dalam jangka panjang.